2022
DOI: 10.1177/14644207221074902
|View full text |Cite
|
Sign up to set email alerts
|

Effect of layer orientation on the single tooth bending fatigue strength of polymer gears manufactured by selective laser sintering

Abstract: This study investigates the influence of tooth layer orientation on the bending fatigue behaviour of Nylon 12 spur gears manufactured by a selective laser sintering process in an ‘on-edge’ configuration. The test gears were submitted to single tooth bending fatigue tests, and the thermal response of gears was recorded using Infrared thermography. The surface morphology of failed teeth was examined using microscopy. The effect of tooth layer orientation on the fatigue strength of selective laser sintering gears… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…The layered structure of the gear helped prevent crack propagation in the PBF-LB/P process. The same authors (Pandian et al , 2022b) have shown that the orientation angle affects the bending fatigue strength. The PBF-LB/P gears manufactured in an on-edge configuration exhibited lower fatigue life than IM gears.…”
Section: Introductionmentioning
confidence: 99%
“…The layered structure of the gear helped prevent crack propagation in the PBF-LB/P process. The same authors (Pandian et al , 2022b) have shown that the orientation angle affects the bending fatigue strength. The PBF-LB/P gears manufactured in an on-edge configuration exhibited lower fatigue life than IM gears.…”
Section: Introductionmentioning
confidence: 99%